Finding patches in a heterogeneous aquatic environment: pH‐taxis by the dispersal stage of choanoflagellates. Issue 2 (23rd March 2017) - Miño, Gastón L.; Koehl, M. A. R.; King, Nicole; Stocker, Roman
Abstract: Microbial eukaryotes that feed on bacteria are critical links in aquatic food webs. We used the choanoflagellate Salpingoeca rosetta, whose life history includes fast‐ and slow‐swimming unicellular forms and multicellular colonies, to study performance of these different forms at finding and accumulating in patches of prey. Video microscopy of behavior in microfluidic experiments showed that only unicellular fast swimmers exhibited taxis into patches of attractant. Of the chemical cues tested, only pH affected behavior: fast swimmers moved toward patches of water that had pH in the range of 6–7 from water with higher or lower pH. Since bacteria can lower the pH of the water in their vicinity, we suggest that seeking regions with a moderately more acidic pH than average seawater helps the fast‐swimming dispersal stage of choanoflagellates find particles or surfaces rich in prey.